The development of a low-cost integrated marine navigation system for leisure crafts and small boats - Mahmud, Mohd. Razali; Ibrahim, Norkhair; Abdul Rahman, Alias; Othman, Rusli; Din, Usmuni; Omar, Abdullah Hisam (UTM, 2005)
Nowadays, most nautical charts are specially produced for large vessels with various equipments and facilities for chart handling. However, such equipments are not available on small boats such as fisherman boats and yachts. In fact, these boats still used conventional nautical charts that are less effective because the data is not up to date. In this technological era with informative community, up to date, interactive information should be given attention in providing contemporary nautical charts. Therefore, a study towards the development of a digital nautical chart database has been carried out to produce vector digital nautical chart for small boat usage, with Geographic Information System (GIS) concept. The conceptual model for the development of digital nautical chart for small boat usage has been implemented that suits with CARIS GIS software environment based on conventional hydrographic chart, MAL 5622 for Langkawi Island. The result of this study can assists users to make many queries such as to find the safest and shortest navigational route with least time period, and identifying obstacles and hazardous areas that should be avoided. Furthermore, this project has developed Web-based GIS system to manage and visualize nautical charts online studies on the creation of Nautical WebGIS for sharing the charts information throughout Malaysia with the latest Notice to Mariners from the Royal Malaysian Navy and Marine Departments. The area of this study covered both MAL 5 (Peninsular Malaysia) and MAL 6 (Sabah and Sarawak). The Nautical WebGIS will enable users to analyses the information through several tools, such as drawing, zooming, searching and viewing reports. In addition, the Nautical WebGIS is evaluated and tested from four aspects, which are Web accessible, Web interface, map display and Web function.